Sex-related difference of association of mitochondrial DNA copy number with PTSD in U.S. service members. (March 2023) - Hu, Xian-Zhang; Ursano, Robert J.; Benedek, David; Li, Xiaoxia; Li, Zhaozhang; Zhang, Lei
Abstract: Gender differences in the lifetime prevalence of post-traumatic stress disorder (PTSD) have been well described with rates reported as approximately 10%–12% in females and 5%–6% in males (Olff, 2017). This study examined whether the sex-related difference of mitochondrial DNA copy number (mtDNAcn), an emerging systemic index of mitochondrial biogenesis and function can serve as a potential biomarker for PTSD. Leukocyte mtDNAcn of service members with PTSD (male = 127, female = 24) or without PTSD (male = 621, female = 78) was assessed using a TaqMan assay. The results were validated by the absolute quantification of QX-200 droplet digital PCR (ddPCR). PTSD symptoms and symptom severity were assessed using the PTSD Checklist (PCL), a 17-item, DSM-based, self-report questionnaire with well-established validity and reliability. DSM-IV criteria and PTSD were determined by PCL total score. We found that mtDNAcn of female subjects with PTSD was significantly higher compared to either male or female non-PTSD controls or male subjects with PTSD (p < 0.05). There was no significant difference in mtDNAcn between males with PTSD and male/female controls without PTSD. Using in vitro cultured SH-SY5Y cells (human neuroblastoma), we demonstrated that estrogen (Estro) treatment significantly decreased mtDNAcn (P < 0.001) compared to the vehicle control. We also found that pre-treatment with either synthetic glucocorticoid dexamethasone (Dex) or Estro blocker tamoxifen (Tamox) attenuated the estrogen-induced decreases of mtDNAcn. Our data suggest that mtDNAcn may be gender-dependent in the Servicemembers with PTSD. Glucocorticoid and/or estrogen receptors may play a role in the regulation of mtDNAcn. The sex-related difference of mtDNAcn may serve as a PTSD biomarker for females.